Sedentary lifestyle, total carbohydrate and added sugar intake, and their association with overweight/obesity in Costa Rican children and adolescents - Núñez Rivas, Hilda Patricia (2025)
Introduction: Childhood overweight and obesity are complex and multifactorial conditions arising from an imbalance between caloric intake and energy expenditure. Methods: A cross-sectional study was conducted involving 2.420 students aged 9 to 17 years from 64 educational centers in Costa Rica. Eating habits were assessed using a validated questionnaire, and Body Mass Index (BMI, kg/m2) was calculated to determine the prevalence of overweight and obesity, classified according to CDC standards. Ethical approval was granted by the Scientific Ethics Committee of INCIENSA, and informed consent was obtained from all participants. To estimate carbohydrate and added sugar intake, three different methods were applied to approximate consumption levels. Descriptive statistics and stepwise regression models were used with statistical significance set at p < 0.05. Results: The prevalence of being overweight and obesity among the students was 27.1% and 16.8%, respectively. The likelihood of being overweight or obese was significantly associated with a higher daily intake of total carbohydrates and added sugars. Key sources of total carbohydrates (accounting for 50.1% to 60.7%) and added sugars (accounting for 73.1% to 88.2%) included foods such as bakery products, cookies and cakes, carbonated beverages, cereals, juices and nectars, and flavored milks. Near 83.8% of children and adolescents in our country consumed more than 10% of their total energy intake from added sugars, exceeding the World Health Organization recommendation (<10% of total energy intake (optimal < 5%). Conclusion: In Costa Rica, there is an urgent need to modify dietary habits through educational initiatives and social awareness campaigns.